The Role of Digital Media in Improving Student Engagement in Islamic Religious Education - Hani Hadiati Pujawardani; Zuraida Zuraida; Soibatul Aslamiah Nasution; Yusriah Yusriah; Trimansyah Trimansyah (Eduprof : Islamic Education Journal, 2026)
The purpose of this research is to analyze the role of digital media in improving student engagement in Islamic Religious Education. The study explores how the integration of digital platforms, interactive applications, and multimedia resources can enhance students’ motivation, participation, and understanding of Islamic values. By employing a qualitative approach, data were collected through literature review and observations of digital learning practices in Islamic education settings. The findings reveal that digital media not only provides innovative methods for delivering religious content but also fosters active involvement, critical thinking, and collaborative learning among students. Moreover, the use of digital tools aligns with the learning styles of the current generation, making Islamic Religious Education more relevant, accessible, and engaging. However, challenges such as digital literacy gaps, limited resources, and the need for proper guidance from educators must also be addressed to maximize the potential benefits. This study highlights the importance of adopting digital media strategically to strengthen students’ religious knowledge and values in a modern learning environment.